Submission of advance payment guarantee as per supplementary agreement no. 1 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of advance payment guarantee as per supplementary agreement no.1 of Brac University new campus development project .